PRACTICE OF LIABILITY MANAGEMENT IN COMMERCIAL BANKS BY ENSURING DEPOSITS STABILITY - Khakimov Sherzod Shukurullaevich (American Journals, 2025)
Deposits account for a significant share of commercial banks' liabilities. Specifically, according to the Republic of Uzbekistan, as of November 1, 2025, the total liabilities of all commercial banks in the Republic amounted to 745,616.0 billion soums, of which deposits accounted for 377,565.0 billion soums, or 50.6 percent. This requires, first and foremost, ensuring deposit stability in commercial banks' liability management.This article determines the share of deposits in the loan portfolio structure of commercial banks in the Republic, their optimal size, and the challenges associated with banks' lending operations. Research proposals aimed at addressing these challenges are developed.